Analisis Yuridis Penyelesaian Sengketa Hak Merek “M6” Antara BMW dan BYD dalam Industri Otomotif (Studi Putusan: Nomor 19/Pdt.Sus-HKI-Merek/2025/PN Niaga Jkt.Pst) - Annisa Fazriani; Anne Gunawati; Jarkasi Anwar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The increasing competition in the global automotive industry has led to potential trademark disputes, one of which is the M6 trademark dispute between BMW and BYD. This study aims to analyze the judges’ legal considerations in Decision Number 19/Pdt.Sus-HKI/Merek/2025/PN Niaga Jkt.Pst and the legal consequences of the decision on the registration of the BYD trademark under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This research uses a normative juridical method by utilizing primary, secondary, and tertiary legal materials collected through library and field research. The results show that the judges’ considerations mainly emphasized formal aspects and did not optimally consider the first to file principle, similarity in essence, and indications of bad faith. The panel of judges also failed to integrate international legal provisions such as the Paris Convention and the TRIPs Agreement in providing protection for well-known trademarks. The decision declaring the lawsuit inadmissible resulted in the substantive issues not being examined, thereby creating legal uncertainty. This condition affects the protection of the exclusive rights of registered trademark owners and indicates that legal protection in resolving trademark disputes has not been effectively implemented.